Right hippocampal volume and attenuated psychotic symptoms distinguish subgroups of youth with common patterns of temporoparietal effective connectivity - Katrina Aberizk; Benson S. Ku; Hengyi Cao; Charles H. Schleifer; Jean M. Addington; Carrie E. Bearden; Kristin S. Cadenhead; Tyrone D. Cannon; Ricardo E. Carrión; Matcheri Keshavan; Daniel H. Mathalon; Diana O. Perkins; et al. (Brain Structure and Function, 2026)
Associations between patterns of brain connectivity and brain structural features have transdiagnostic relevance to psychopathology. There is considerable evidence for disruptions to the hippocampus and temporoparietal brain systems in psychotic disorders. The present study examines structure–function relationships—specifically, the relation of hippocampal volume with patterns of temporoparietal effective connectivity—in youth at clinical high-risk for psychosis (CHR-P) and healthy controls (HCs). Participants at CHR-P and HCs completed clinical symptom measures and magnetic resonance imaging at baseline ( n = 388, 42.5% female, age = 19.8 ± 4.2) in the second cohort of the North American Prodrome Longitudinal Study. Group Iterative Multiple Model Estimation established a common functional network of temporoparietal effective connectivity in the full sample. Next, supervised (assuming the CHR-P and HC groups represent classes) and unsupervised (data-driven) clustering procedures interrogated effective connectivity parameters relevant to subsamples. Mean difference tests by unsupervised cluster membership determined whether clusters formed based on temporoparietal effective connectivity differed in hippocampal volume. Clusters were also compared on representation of CHR-P and positive and negative symptom totals to determine whether unsupervised clustering recovered clinical features. Unsupervised clustering generated two clusters that differed significantly in right hippocampal volume and attenuated positive and negative symptoms with small-to-medium effect sizes. The cluster demonstrating reduced right hippocampal volume reported greater symptoms. Unsupervised clustering did not recover diagnostic groups. Findings are consistent with literature indicating the transdiagnostic relevance of hippocampal volume to organizational properties of brain functional networks and patterns of temporoparietal connectivity.

Alterations in Gray Matter Structure Linked to Frequency-Specific Cortico-Subcortical Connectivity in Schizophrenia via Multimodal Data Fusion - Marlena Duda; Ashkan Faghiri; Aysenil Belger; Juan R. Bustillo; Judith M. Ford; Daniel H. Mathalon; Bryon A. Mueller; Godfrey D. Pearlson; Steven G. Potkin; Adrian Preda; Jing Sui; Theo G. M. Van Erp; et al. (Neuroinformatics, 2025)

Ruminative reflection is associated with anticorrelations between the orbitofrontal cortex and the default mode network in depression: implications for repetitive transcranial magnetic stimulation - Tobin J. Ehrlich; Jyoti Bhat; Andrea M. Horwege; Daniel H. Mathalon; Gary H. Glover; Brian J. Roach; Bashar W. Badran; Steven D. Forman; Mark S. George; J. Cobb Scott; Michael E. Thase; Jerome A. Yesavage; et al. (Brain Imaging and Behavior, 2022)
Patients with depression who ruminate repeatedly focus on depressive thoughts; however, there are two cognitive subtypes of rumination, reflection and brooding, each associated with different prognoses. Reflection involves problem-solving and is associated with positive outcomes, whereas brooding involves passive, negative, comparison with other people and is associated with poor outcomes. Rumination has also been related to atypical functional hyperconnectivity between the default mode network and subgenual prefrontal cortex. Repetitive pulse transcranial magnetic stimulation of the prefrontal cortex has been shown to alter functional connectivity, suggesting that the abnormal connectivity associated with rumination could potentially be altered. This study examined potential repetitive pulse transcranial magnetic stimulation prefrontal cortical targets that could modulate one or both of these rumination subtypes. Forty-three patients who took part in a trial of repetitive pulse transcranial magnetic stimulation completed the Rumination Response Scale questionnaire and resting-state functional magnetic resonance imaging. Seed to voxel functional connectivity analyses identified an anticorrelation between the left lateral orbitofrontal cortex (−44, 26, −8; k = 172) with the default mode network-subgenual region in relation to higher levels of reflection. Parallel analyses were not significant for brooding or the RRS total score. These findings extend previous studies of rumination and identify a potential mechanistic model for symptom-based neuromodulation of rumination.

ENIGMA + COINSTAC: Improving Findability, Accessibility, Interoperability, and Re-usability - Jessica A. Turner; Vince D. Calhoun; Paul M. Thompson; Neda Jahanshad; Christopher R. K. Ching; Sophia I. Thomopoulos; Eric Verner; Gregory P. Strauss; Anthony O. Ahmed; Matthew D. Turner; Sunitha Basodi; Judith M. Ford; et al. (Neuroinformatics, 2022)
The FAIR principles, as applied to clinical and neuroimaging data, reflect the goal of making research products F indable, A ccessible, I nteroperable, and R eusable. The use of the Collaborative Informatics and Neuroimaging Suite Toolkit for Anonymized Computation (COINSTAC) platform in the Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) consortium combines the technological approach of decentralized analyses with the sociological approach of sharing data. In addition, ENIGMA + COINSTAC provides a platform to facilitate the use of machine-actionable data objects. We first present how ENIGMA and COINSTAC support the FAIR principles, and then showcase their integration with a decentralized meta-analysis of sex differences in negative symptom severity in schizophrenia, and finally present ongoing activities and plans to advance FAIR principles in ENIGMA + COINSTAC. ENIGMA and COINSTAC currently represent efforts toward improved Access, Interoperability, and Reusability. We highlight additional improvements needed in these areas, as well as future connections to other resources for expanded Findability.

Age affects temporal response, but not durability, to serial ketamine infusions for treatment refractory depression - Steven Pennybaker; Brian J. Roach; Susanna L. Fryer; Anusha Badathala; Art W. Wallace; Daniel H. Mathalon; Tobias F. Marton (Psychopharmacology, 2021)

Cross-paradigm connectivity: reliability, stability, and utility - Hengyi Cao; Oliver Y. Chen; Sarah C. McEwen; Jennifer K. Forsyth; Dylan G. Gee; Carrie E. Bearden; Jean Addington; Bradley Goodyear; Kristin S. Cadenhead; Heline Mirzakhanian; Barbara A. Cornblatt; Ricardo E. Carrión; et al. (Brain Imaging and Behavior, 2021)

ADHD and cannabis use in young adults examined using fMRI of a Go/NoGo task - Jerod Rasmussen; B. J. Casey; Theo G. M. van Erp; Leanne Tamm; Jeffery N. Epstein; Claudia Buss; James M. Bjork; Brooke S. G. Molina; Katerina Velanova; Daniel H. Mathalon; Leah Somerville; James M. Swanson; et al. (Brain Imaging and Behavior, 2016)

Go/No Go task performance predicts cortical thickness in the caudal inferior frontal gyrus in young adults with and without ADHD - Erik Newman; Terry L. Jernigan; Krista M. Lisdahl; Leanne Tamm; Susan F. Tapert; Steven G. Potkin; Daniel Mathalon; Brooke Molina; James Bjork; F. Xavier Castellanos; James Swanson; Joshua M. Kuperman; et al. (Brain Imaging and Behavior, 2016)

Frontally mediated inhibitory processing and white matter microstructure: age and alcoholism effects - Ian M. Colrain; Edith V. Sullivan; Judith M. Ford; Daniel H. Mathalon; Selwyn-Lloyd McPherson; Brian J. Roach; Kate E. Crowley; Adolf Pfefferbaum (Psychopharmacology, 2011)

Working Memory Overload: Fronto-Limbic Interactions and Effects on Subsequent Working Memory Function - Richard J. Yun; John H. Krystal; Daniel H. Mathalon (Brain Imaging and Behavior, 2010)

Fore-period effect and stop-signal reaction time - Chiang-Shan Ray Li; John H. Krystal; Daniel H. Mathalon (Experimental Brain Research, 2005)

NMDA receptor antagonist effects, cortical glutamatergic function, and schizophrenia: toward a paradigm shift in medication development - John H. Krystal; D. Cyril D'Souza; Daniel Mathalon; Edward Perry; Aysenil Belger; Ralph Hoffman (Psychopharmacology, 2003)